Non-thermal pressure in the outskirts of Abell 2142. Issue 1 (20th December 2017) - Fusco-Femiano, Roberto; Lapi, Andrea
Abstract: Clumping and turbulence are expected to affect the matter accreted on to the outskirts of galaxy clusters. To determine their impact on the thermodynamic properties of Abell 2142, we perform an analysis of the X-ray temperature data from XMM–Newton via our SuperModel, a state-of-the-art tool for investigating the astrophysics of the intracluster medium already tested on many individual clusters (since Cavaliere, Lapi & Fusco-Femiano 2009 ). Using the gas density profile corrected for clumpiness derived by Tchernin et al. (2016 ), we find evidence for the presence of a non-thermal pressure component required to sustain gravity in the cluster outskirts of Abell 2142, that amounts to about 30 per cent of the total pressure at the virial radius. The presence of the non-thermal component implies the gas fraction to be consistent with the universal value at the virial radius and the electron thermal pressure profile to be in good agreement with that inferred from the SZ data. Our results indicate that the presence of gas clumping and of a non-thermal pressure component are both necessary to recover the observed physical properties in the cluster outskirts. Moreover, we stress that an alternative method often exploited in the literature (included Abell 2142) to determine the temperature profile k B T  =  P e / n e basing on a combination of the Sunyaev–Zel'dovich (SZ) pressure P e and of the X-ray electron density n e does not allow us to highlight the presence of non-thermal pressure support in the cluster outskirts.